GAYA HIDUP SEKSUAL WARIA NON PEKERJA SEKS KOMERSIAL KOTA SEMARANG - Dewi Rokhmah; Yennike Tri Herawati (Jurnal Ilmu Kesehatan Masyarakat, 2010)
Being transvestites is not merely bringing a biological problems, but also psychological and sociological. Most transvestites were having a low self concept due to their confusion on their sexual identity. The ambiguity place them isolated from community. Social pressure forms stigmatization and discrimination toward thisgroup of people, which lead them to have more risky sexual practice. This study aims to analize the sexual life style of non-commercial transvestites in Semarang. It was a qualitative study involved informants aged 25-54. Most of them reconstruct their face and body in order to maximize their sexual appeal as a female. Most of respondents were having steady single or married partner. However, the status was not limiting them to have sexual relationship with others. Less respondent found their partner from chatting, hang-out in a hot spot (cebongan), and using gigolos services. All the respondents only needed a few of time to finally engage in sexual intercourse with their partner. First sight, first date and sexual intercourse were occurred in a quick encounter. The reasons of having sexual intercourse (anal and or oral sex) were to show their love to their partner and just for fun. They were mostly prefer anal or oral sex, however, some of them also practicing petting with “es gosrok” style of commonly called clamping style. Although most of them negotiate with their partner to use condom, there were some of them were not because they did not practicing penetration anal sex. Keywords : transvestites, non-commercial, sexual lifestyle, sexual script